Indium(III)-Catalyzed Reduction of Nitrobenzenes to Anilines: Scope and Limitations - Sakai, Norio; Asama, Shun; Konakahara, Takeo; Ogiwara, Yohei (Synthesis, 2015)
We have demonstrated that a combination of indium(III) iodide and 1,1,3,3-tetramethyldisiloxane (TMDS) effectively catalyzes the chemoselective reduction of nitrobenzenes with a variety of functional groups (halogens, alkyl, alkoxy, hydroxy, ester, amino, amide, cyanide, thiol, and an alkene moiety), producing the corresponding aniline derivatives.
Keywords: indium; reduction; hydrosiloxanes; nitrobenzenes; anilines